A rare case of sirenomelia with total bilateral cleft lip palate and kyphoscoliosis - Arya, Sangeeta; Verma, Anil Kumar; Pandey, Kiran; Verma, Sunil Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Sirenomelia, a rare congenital deformity, has fused lower limbs with variable combination of visceral anomalies. This condition is fatal within a day or two of birth so early antenatal detection and pregnancy termination is advocated. Antenatally it can be diagnosed by ultrasonography showing oligohydramnios, renal agenesis and fibulae positioned between the tibiae. A 24 years old Muslim primigravida came for first antenatal check up at 18 weeks of pregnancy. She didn’t turn up and came directly in emergency at 37 weeks in active labor and delivered a baby weighing 1.8 kg with a small sized placenta, complete bilateral cleft lip palate, Kyphoscoliosis and fused lower limbs upto ankles. Baby expired after 25 minutes of birth. Till now around 300 cases of Sirenomelia have been reported worldwide. All human cases of Sirenomelia have been found to be associated with variable degree of renal and urethral dysplasia or renal agenesis. External genitalia are affected, whereas gonads remain unaffected. In rare cases Sirenomelia is associated with upper body defects including cleft palate, cervical and upper thoracic vertebral abnormalities, pulmonary hypoplasia and cardiac defects.